Validation of the Resilience Scale for Adolescents (READ) in Ireland: a multi‐group analysis. Issue 2 (29th April 2016) - Kelly, Yvonne; Fitzgerald, Amanda; Dooley, Barbara
Abstract: Resilience is a process reflecting positive adaptation in the face of adversity. The Resilience Scale for Adolescence (READ) incorporates intrapersonal and interpersonal protective factors mapping onto the three salient domains of resilience, including individual, family and external environment. This study investigated the validity and reliability of the READ by means of factor analysis, multi‐group analysis, inter‐correlations and internal consistency measures. Participants were 6085 young people in Ireland aged 12–18 years. Participants completed the My World Survey – Second Level (MWS‐SL), assessing risk and protective factors of mental health. Confirmatory factor analysis validated the original five‐factor structure of the READ including Personal Competence, Social Competence, Structured Style, Family Cohesion, and Social Resources, χ 2 (340) = 6146.02, p < 0.001, RMSEA = 0.056 (90% CI = 0.054–0.057), CFI = 0.97; GFI = 0.93. Measurement invariance indicated that the five‐factor structure was similar across gender, school cycle and distress levels. Construct validity was evident, by correlating the five factors of the READ with various social, psychological and behavioural variables. The findings suggest that the READ is a valid measure to assess resilience factors among adolescents in Ireland, demonstrating its applicability in a different cultural context and with a wider age range of adolescents. Copyright © 2016 John Wiley & Sons, Ltd.